Nanomaterials-Incorporated Chemically Modified Gelatin Methacryloyl-Based Biomedical Composites: A Novel Approach for Bone Tissue Engineering - Abigail Herrera-Ruiz; Benjamín Betancourt Tovar; Rubén Gutiérrez García; María Fernanda Leal Tamez; Narsimha Mamidi (MDPI AG, 2022)
Gelatin methacryloyl (GelMA)-based composites are evolving three-dimensional (3D) networking hydrophilic protein composite scaffolds with high water content. These protein composites have been devoted to biomedical applications due to their unique abilities, such as flexibility, soft structure, versatility, stimuli-responsiveness, biocompatibility, biodegradability, and others. They resemble the native extracellular matrix (ECM) thanks to their remarkable cell-adhesion and matrix-metalloproteinase (MMP)-responsive amino acid motifs. These favorable properties promote cells to proliferate and inflate within GelMA-protein scaffolds. The performance of GelMA composites has been enriched using cell-amenable components, including peptides and proteins with a high affinity to harmonize cellular activities and tissue morphologies. Due to their inimitable merits, GelMA systems have been used in various fields such as drug delivery, biosensor, the food industry, biomedical, and other health sectors. The current knowledge and the role of GelMA scaffolds in bone tissue engineering are limited. The rational design and development of novel nanomaterials-incorporated GelMA-based composites with unique physicochemical and biological advantages would be used to regulate cellular functionality and bone regeneration. Substantial challenges remain. This review focuses on recent progress in mitigating those disputes. The study opens with a brief introduction to bone tissue engineering and GelMA-based composites, followed by their potential applications in bone tissue engineering. The future perspectives and current challenges of GelMA composites are demonstrated. This review would guide the researchers to design and fabricate more efficient multifunctional GelMA-based composites with improved characteristics for their practical applications in bone tissue engineering and biomedical segments.